2021
DOI: 10.1155/2021/9937293
|View full text |Cite
|
Sign up to set email alerts
|

Pavement and Noise Reduction Performance of Open‐Graded Asphalt Friction Course Improved by Waste Tire Crumb Rubber

Abstract: To further reveal the road performance and noise reduction performance of open-graded friction course (OGFC), the crumb rubber prepared by adding waste tires were considered, and the performance requirements of the material were put forward. To avoid the influence of rubber particle swelling on aggregate, the special gradation and mix proportion of OGFC mixture were designed, and the particle size of 4.75 mm was proposed as the control size. The test results show that the aggregate forms a good embedded struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…When PAM is used as a friction course on roadway surface, it helps to reduce the hydroplaning potential of vehicles traveling during rain and thus lowers the risk of wet weather crashes. As an additional benefit, the PAM pavement surface can lower traffic noise in comparison to dense-graded asphalt (DGA) pavement surface [9].…”
Section: Introductionmentioning
confidence: 99%
“…When PAM is used as a friction course on roadway surface, it helps to reduce the hydroplaning potential of vehicles traveling during rain and thus lowers the risk of wet weather crashes. As an additional benefit, the PAM pavement surface can lower traffic noise in comparison to dense-graded asphalt (DGA) pavement surface [9].…”
Section: Introductionmentioning
confidence: 99%
“…As regards binder properties, polymers, CR, and warm mix asphalt (WMA) additives have also been evaluated to improve the mix durability against raveling and cracking ( 14 ). In addition, the use of CR promotes OGFC’s ability to reduce tire–pavement noise ( 15 ). It was also reported that the use of fillers as a binder modifier has resulted in a considerable improvement in mix performance ( 16 , 17 ).…”
mentioning
confidence: 99%